India's intellectual traditions and contributions to the world - Singh, Bal Ram (World Association for Vedic Studies ; D.K. Printworld, 2010)
Contributed articles selected from papers presented at the fourth International Conference on "India's Contributions and Influences to Solve the World's Current Problems, held at University of Massachusetts, Dartmouth during 12-14 July 2002 and fifth International Conference on "India's Intellectual Traditions in Contemporary Global Context", held at University of Maryland, Shady Grove Campus during 9-11 July 2004 moderated by WAVES.